TINDAKAN HUKUM TERKAIT PERILAKU BULYING REMAJA SMP DI WILAYAH KABUPATEN BATUBARA - Azzahara nasution (Al Qadhi, 2023)
Legal aid related to adolescent bullying behaviour is an important aspect in protecting personal rights and solving social problems that are often faced by adolescents. The purpose of this study is to analyse and describe the legal actions that can be applied in relation to adolescent bullying behaviour. The method used is descriptive analysis, collecting information from various literatures, legal regulations and related research results. The results of this study show that several legal measures can be taken to overcome bullying among adolescents, including: 1. Preventive action: Education and information on the negative impacts of bullying, the creation of anti-bullying policies in schools and communities, and the involvement of families and communities in solving the problem. 2. Referrals: Involvement of authorities such as teachers, parents and police in guiding and helping victims and perpetrators of bullying. In addition, bullying prevention training and counselling are also organised for the younger generation. 3. Punishment: If the harassment is serious and unlawful, penalties may be imposed in accordance with applicable laws and regulations. This includes both criminal and civil actions such as criminal prosecution, claims for damages or remedies. However, it is also important to note that addressing youth bullying involves not only legal action, but also social, educational and counselling approaches.